Elaboration and evaluation of maqui juice (Aristotelia chilensis (Mol.) Stuntz) by steam drag - Araneda, Ximena (2014)
The aim of this study was develop and evaluate maqui juice (Aristotelia chilensis (Mol.) Stuntz), to be potentially considered as a functional beverage of natural origin, without chemical additives and minimally processed, using the technique of steam drag of type artisanal. Fruit harvested manually was used in the Region of The Araucanía (Chile). Two juice concentrates with sugar and without sugar were produced. Analyzes such as were conducted: content of soluble solids, pH, acidity, moisture content, dry matter (DM), total ash, total sugars (AT), crude protein (PC), total polyphenols (PFT) and total carbohydrates (CHT), the polyphenol content highlighting for unsweetened juice with 993.2 mg 100 mL-1 EAG and juice with sugar 829.208 mg 100 mL-1 EAG. Therefore, the technique allows to extract juice with minimal processing machin, presenting this high concentration of polyphenols.